Climatic responses and variability in bark anatomical traits of 23 Picea species - Nie, Wen; Dong, Yao; Liu, Yifu; Tan, Cancan; Wang, Ya; Yuan, Yanchao; Ma, Jianwei; An, Sanping; Liu, Jianfeng; Xiao, Wenfa; Jiang, Zeping; Jia, Zirui; et al. (Frontiers in Plant Science, 2023)
In woody plants, bark is an important protective tissue which can participate in photosynthesis, manage water loss, and transport assimilates. Studying the bark anatomical traits can provide insight into plant environmental adaptation strategies. However, a systematic understanding of the variability in bark anatomical traits and their drivers is lacking in woody plants. In this study, the bark anatomical traits of 23 Picea species were determined in a common garden experiment. We analyzed interspecific differences and interpreted the patterns in bark anatomical traits in relation to phylogenetic relationships and climatic factors of each species according to its global distribution. The results showed that there were interspecific differences in bark anatomical traits of Picea species. Phloem thickness was positively correlated with parenchyma cell size, possibly related to the roles of parenchyma cells in the radial transport of assimilates. Sieve cell size was negatively correlated with the radial diameter of resin ducts, and differences in sieve cells were possibly related to the formation and expansion of resin ducts. There were no significant phylogenetic signals for any bark anatomical trait, except the tangential diameter of resin ducts. Phloem thickness and parenchyma cell size were affected by temperature-related factors of their native range, while sieve cell size was influenced by precipitation-related factors. Bark anatomical traits were not significantly different under wet and dry climates. This study makes an important contribution to our understanding of variability in bark anatomical traits among Picea species and their ecological adaptations.